The Un-Intended Convergence: How the Finnish Unemployment Reached the European Level - Erkki Koskela; Roope Uusitalo (Center for Economic Studies and ifo Institute (CESifo), 2003)
The Finnish unemployment rose in the early 1990's from three to eighteen percent in four years. Unemployment has then decreased to the average European level, being 8.5 percent in October 2002. In this paper, we describe the shocks leading to this unforeseen increase in unemployment. We then discuss the role of labour market institutions in the adjustment process that has brought unemployment back to normal' levels. We argue that these institutions cannot be blamed for the increase in unemployment, but that more flexible institutions could have lead to a more rapid decline in unemployment.
Keywords: 330; unemployment; labour market institutions